Academic Correlates of Unwanted Sexual Contact, Intercourse, Stalking, and Intimate Partner Violence: An Understudied but Important Consequence for College Students - Banyard, Victoria L.; Demers, Jennifer M.; Cohn, Ellen S.; Edwards, Katie M.; Moynihan, Mary M.; Walsh, Wendy A.; Ward, Sally K. (Journal of interpersonal violence, 2020)
Sexual assault, partner abuse, and stalking are major problems on college campuses. Past research has demonstrated a host of physiological and psychological outcomes associated with victimization; however, there has been little research conducted on the potential academic outcomes associated with victimization. The purpose of this study was to measure the relation between academic outcomes and experiences of sexual violence, intimate partner violence, and stalking victimization among college students. A sample of 6,482 undergraduate students currently enrolled at one of eight universities in New England was surveyed using items from the subscales of the College Persistence Questionnaire (Academic Efficacy, Collegiate Stress, Institutional Commitment, and Scholastic Conscientiousness). All four types of victimization were associated with significant differences on academic outcomes after controlling for sex and year in school, with victimized students reporting lower academic efficacy, higher college-related stress, lower institutional commitment, and lower scholastic conscientiousness. Polyvictimization was also significantly correlated with outcomes, with the greater number of types of victimization experienced by students being associated with more negative academic outcomes. Implications for future research and campus response were discussed.